PENEGAKAN HUKUM DI KAWASAN ALUR LAUT KEPULAUAN INDONESIA (ALKI) MENURUT KONSEPSI HUKUM INTERNASIONAL DAN HUKUM NASIONAL INDONESIA - Richard Marsilio Waas (SASI, 2016)
Indonesia is an archipelago consisting of 17,504 islands with the second longest coastline in the world after Canada. Indonesian territory that stretches from Sabang to Merauke composed of 1/3 and 2/3 of the ocean and the mainland after Indonesia ratified UNCLOS in 1982. Based on Law No. 17 of 1985, the extent to 7.9 million km2 comprising of 2 million km2 of land and 5.9 million km2 of ocean. Because Indonesia has good sea area that is subject to the sovereignty and are subject to or falls below the rights and territorial region. In addition to have ratified the Convention on the Law of the Sea 1982 (UNCLOS) Indonesia has also been transformed into Law No. 6 of 1996 and the subsequent Indonesian Government Regulation No. 37 of 2002 on the rights and obligations of foreign ships and aircraft in exercising the right of archipelagic sea lanes passage through archipelagic sea lanes set. Government Regulation No. 38 of 2002 also enhance the rules on listing Baselines of Indonesia where the establishment of ALKI also based on Law No. 17 of 1985 in addition to the Law No. 43 Year 2008 on the territory of the State as well as for guidance in enforcing the law in the territory of the Republic of Indonesia. Importance of the sea in the relations between nations led to the important role of international maritime law, because of the law, among others define the limits of state sovereignty coastal or island states in managing and utilizing sea space especially sea area under the sovereignty such as the territorial sea and archipelagic waters, Archilepagic Sea island nation is the right to give a right of passage for vessels in exercising the right of archipelagic sea lanes passage through predefined. In addition to the island nation that has the right to ensure the safety of crossing ALK passer, passer also have rights and obligations if doing track in the archipelagic sea lane, while respecting the legal provisions in force nationally in a State.